Colors of athletic uniforms how they can affect the athlets' aggression, motivation, and ideal performance state. - Alingasa, Aniceta Patricia T.
This study was conducted to determine how colors of athletic uniforms can affect the athlete's aggression, motivation and Ideal Performance State. Sixteen (16) members of West Visayas State University's basketball varsity team were the participants of this study. A series of experiments and a set of scales were made for the participants to answer in order to gather necessary data in analyzing their responses. The results of the study showed that athletes have different emotional responses to colors and warm domain were blue and orange respectively. There is no significant effect between color of athletic uniform and motivation, as well as aggression. It is found that the color blue fosters a more well-developed Ideal Performance State than the color orange.